Ceramic ball pen and mathematical modelling. (4th February 2010) - Zeng, Ke; Yang, Jinlong; Xi, Xiaoqing
In pen industry, ball pens are becoming more and more popular and its market is growing bigger. However, the technology concerned with ball pens, especially gel ink ball pens, is not mature yet. In this paper, several factors influence the performance of ball pens are taken into account. Such factors include: the material of the ball, the clearance, the bowl holds the ball and the speed of writing. The system of providing ink and flowing ink are also calculated. Meanwhile, a model to describe the process is made. The results calculated by the model basically fit the actual instance.